Decommissioning Disputes – The Sustainability Gap - Balogun, Timi; Davar, Michael; Chicco, Ruggero (Journal of Sustainable Development Law and Policy, 2025)
The regulatory framework for oil and gas decommissioning forms the background against which decommissioning disputes take place. The growing role of sustainability considerations in the decommissioning process could lead to an increase in existing decommissioning disputes and to the development of new decommissioning sustainability disputes.